Brand Attachment As A Driver Of Influencer Authority - Nagarista, Maria Magdalena Leony; Setiono, Bambang (Journal of Business, Management, and Social Studies, 2021)
Objective – This study examines how influencers as a new marketing strategy to increase brand attachment and brand love from customers through perceived quality, personal branding, and brand personality with a case study of Arief Muhammad’s business, Billionaire’s Project. Methodology – Using SmartPLS software as a tool to examine validity and reliability, this study is quantitative in nature and 185 people in all took part in the survey for this study. Findings – The result highlights the brand attachment is the main variable that can influence influencer authority capital for influencers to be able to increase influence on customers to be bonded to traded brands. Novelty – This study contributes to a deeper understanding of how these factors interact to influence consumer behavior in the context of influencer marketing.